Cooperative Exchange with Substitutable Ties and Its Competitive Outcomes - 배종훈 (Seoul Journal of Business, 2011)
With a model of tie substitution, a construct that reflects each actor's evaluation of his or her social relations or networks, this study proposes that each actor's subjective evaluation of objective structural constraints may facilitate or delay the realization of structural constraints in general and the division of cooperative benefits in particular. It shows the following: first, ego with few (perceived) substitutable ties is likely to accept the unequal allocation of cooperative benefits; second, symmetry in tiesubstitution at the global network suppresses (aggravates) competition for the division of cooperative outcomes when individual tie-substitution is low (high). [PUBLICATION ABSTRACT]